Strategic foresight: Using the "ETUI future scenarios for 2050" to respond more effectively to multiple crises - Aída Ponce Del Castillo; Patricia Lustig (European Trade Union Institute (ETUI), 2023)
The multiple crises that the world is facing have diverse and unequal impacts on society at large. Uncertainty reigns as these crises continuously evolve in many different directions. The fast-paced change that we are experiencing challenges societal structures and triggers social unrest. Foresight and scenarios can be useful tools to improve our response to these crises from a long-term perspective. This report starts by explaining how foresight and future scenarios can help to anticipate how to best respond to crises, feed evidence-based policy-making and foster innovation. They can also help organisations of all types and sizes to take coherent and robust action. The report argues that strategic foresight needs to be implemented as a new layer of organisational change. The report then describes the ETUI future scenarios developed in 2020: (1) High-Tech Hives; (2)(Dis)-connected Ghettos; (3) Green Castles; and (4) Eco-Villages, explaining the foresight methodology used to develop them. In order to bring the scenarios up to date, the text maps some of the key events that took place in 2021 and 2022, focusing on the four global crises: climate and energy; rising inflation; war and changing geopolitical order; and social inequalities. To encourage people to use the ETUI scenarios, the report provides guiding questions to help the reader to recognise whether a given scenario is starting to materialise. It identifies key issues that need to be monitored in the coming years. Finally, the text highlights the fact that strategic foresight does not end with the development of future scenarios, and that a foresight process also requires action plans, including roadmaps and contingency plans. It concludes by inviting readers to use the scenarios in their own work environment.
Keywords: 330